Penggunaan Media Surat Kabar Daring untuk Meningkatkan Keterampilan Menulis Teks Editorial Siswa Kelas XII SMA Negeri 3 Sinjai - Asman Asman; Umar Mansyur; Rahmat Rahmat (Departement of Mathematics Education, 2024)
This research aims to improve the editorial text writing skills of class XII students at SMA Negeri 3 Sinjai. This research is Classroom Action Research (PTK). The subjects of this research were all students of class XII MIPA 3 SMA Negeri 3 Sinjai, totaling 30 students. The data collection techniques used are observation and tests. The data from this research were analyzed using qualitative analysis and quantitative analysis. The process of writing editorial texts using online newspaper media for class students XII MIPA 3 UPT SMA Negeri 3 Sinjai first cycle of the first meeting obtained student activity of 63% while at the second meeting it increased to 65%, then in cycle II, at the first meeting, student activity was 74% and at the second meeting it increased to 79%. Results of writing editorial texts using online newspaper media for class students XII MIPA 3 UPT SMA Negeri 3 Sinjai cycle I obtained an average score of 73,13 with a percentage of 60% of students who completed, while in cycle II the average score of students was 78,36 with a percentage of 87% who completed. Therefore, it can be concluded that the use of online newspaper media to improve the editorial text writing skills of class XII MIPA 3 UPT SMA Negeri 3 Sinjai students was declared successful.